Modulus of Elasticity Loss as a Rapid Indicator of Rot-fungal Attack on Untreated and Preservative-treated Wood in Laboratory Tests - Xingxia Ma; Grant T. Kirker; Carol A. Clausen; Mingliang Jiang; Haibin Zhou (BioResources, 2017)
The modulus of elasticity (MOE) of wood is a sensitive indicator of rot-fungal attack. To develop an alternative method of rapid assessment of fungal decay in the laboratory, changes in static MOE of untreated and preservative-treated wood were measured during exposure to the brown-rot fungus, Gloeophyllum trabeum, and the white-rot fungus, Trametes versicolor, in a standard soil bottle assay. Static MOE loss was compared with mass loss. The results showed that the MOE of wood was a sensitive and reliable indicator of rot-fungal attack, regardless of fungus or wood species. The MOE analysis of untreated wood reduced the 12- to 16-week exposure time necessary for the standard mass loss measurement to four weeks. Also, the exposure time for preservative-treated wood was reduced to eight weeks. Untreated wood was determined to be susceptible to decay if the MOE loss was 40% or more after a four-week exposure, while treated wood was considered susceptible to decay if the MOE loss was 40% or more after an eight-week exposure.